The Cell Wall of Seagrasses: Fascinating, Peculiar and a Blank Canvas for Future Research - Pfeifer, Lukas; Classen, Birgit (Frontiers in Plant Science, 2020)
Seegrasses are a polyphyletic group of angiosperm plants, which evolved from early monocotyledonous land plants and returned to the marine environment around 140 million years ago. Today, seagrasses comprise the four families Zosteraceae, Hydrocharitaceae, Posidoniaceae and Cymodoceaceae and form important coastal ecosystems worldwide. Despite of this ecological importance, the existing literature on adaption of these angiosperms to the marine environment and especially their cell wall composition is limited up to now. A unique feature described for some seagrasses is the occurrence of polyanionic, low-methylated pectins mainly composed of galacturonic acid and apiose (apiogalacturonans). Furthermore, sulfated galactans have been detected in some species. Recently, arabinogalactan-proteins, highly glycosylated proteins of the cell wall of land plants, have been isolated for the first time from a seagrass of the baltic sea. Obviously, seagrass cell walls are characterized by new combinations of structural polysaccharide and glycoprotein elements known from macroalgae and angiosperm land plants. In this review, current knowledge on cell walls of seagrasses is summarized, information on identical or different strategies of seagrasses for osmoregulation are discussed and suggestions for future investigations are given.